Inovasi pengolahan limbah plastik dan desain kemasan kreatif untuk peningkatan daya saing usaha mikro, kecil, dan menengah di Kelurahan Tuah Madani - Jamilah, Putri; Elisabeth, Mayline; Hartanto, Pandu Tri; Muyadi, Nanang (Penamas: Journal of Community Service, 2024)
The problem of plastic waste is an urgent global issue today. Plastic waste is a type of waste that takes a very long time to decompose, so by accumulating plastic waste, it will become a waste that will damage natural ecosystems, both in the ocean and on land. This service activity aims to provide innovative solutions through integrated counseling that combines the transformation of plastic waste into value-added products with creative packaging design. This activity focuses on MSMEs as business actors with great potential in managing plastic waste. Through a series of trainings and workshops, MSMEs are expected to be able to increase productivity, competitiveness, and environmental awareness. The results of this activity show an increase in the ability of MSMEs to process plastic waste, create new, unique products, and increase income. In addition, this activity also succeeded in increasing public awareness of the importance of sustainable plastic waste management.